Legal aspects of hotel tax collection using the online system in Badung District government - Wiranata, I Gede Ari Putra (International Journal Labs, 2024)
The aim of this study is to discuss the legal aspects of hotel tax collection using an online system in the Badung Regency Government. The study provides insights into how digitalization of tax systems can impact local governance, compliance, and efficiency, offering a valuable case study for other regions considering similar implementations. The results of the study show that there is a significant increase in tax revenues from 2022 to 2023, mainly due to the post-pandemic recovery of the tourism sector in Badung. With the right strategy, this system can become an important component in modern public financial management and is responsive to future challenges. With sustainable technological infrastructure development and strict supervision, online tax collection can become a tool in encouraging economic growth and community welfare. Comparative studies between regions that have implemented similar online tax systems could provide valuable insights into best practices, challenges, and scalability.